KEGAGALAN DALAM PENEGAKAN HUKUM LINGKUNGAN HIDUP - Yudistiro Yudistiro (Komisi Yudisial RI, 2011)
ABSTRACTPT. KH producing textile and fabric did not follow the requirements set out in Government Regulation No. 85 Year 1999 on Management of Hazardous and Toxic Waste. Its production of solid waste/sludge contained metals pollution. The judge set the defendant, the Director of PT KH free from the primary charge of Article 43 paragraph (1) of Law No. 23 of 1997, but punished the defendant with the indictment of Article 44 paragraph (1) of Law No. 23 of 1997. In deciding the case, the panel of judges did not optimize the role of expert witnesses and use the results of laboratory analysis report on solid waste samples examined by the laboratory of ALS Bogor. According case above, environmental law has grown rapidly, not only concerning the function of law in keeping control and certainty for the community (social control), but also the role as the agent of stability.Keywords: laboratory, expert witnesses, environmental pollution ABSTRAKPT. KH memproduksi tekstil dan kain tetapi tidak mengikuti syarat yang ditetapkan oleh Peraturan Pemerintah Nomor 85 Tahun 1999 tentang Manajemen Pengelolaan Limbah Bahan Berbahaya dan Beracun. Kasus ini dibawa ke pengadilan, dan hakim memutuskan terdakwa, Direktur PT KH, bebas dari dakwaan primair sebagaimanan Pasal 43 paragraph (1) UU Nomor 23 Tahun 1997, tetapi menghukum terdakwa melanggar Pasal 44 paragraph (1) UU Nomor 23 Tahun 1997. Menurut penulis, dalam memutuskan perkara, majelis hakim tidak optimal mengunakan peran saksi ahali dan hasil test laboratorium dari ALS Bogor sebagai alat bukti. Kasus di atas salah satu kasus hukum lingkungan yang dibawa kepengadilan karena seiring pesatnya perkembangan dan menjadi perhatian pemerintah, komunitas sosial, dan juga peran unsur lain untuk berperan menjaga stabilitas lingkungan.Kata kunci: laboratorium, saksi ahli, polusi lingkungan